(untitled) (Journal of Philosophy, Culture and Political Science, 2023)
The study of the problems of integration cooperation of Kazakhstan with other international actors in the Eurasian space is becoming particularly acute. Political and international problems and shifts arising at the top table of world affairs do not bypass the Eurasian region, which affects the interests of international actors of the Eurasian space. The factors that have influenced the growth of interest in integration issues in the present period are primarily related to the reconstruction of the world policy: the ongoing global changes, global crises, geopolitical disagreements and conflicts negatively affect the integration structures and their further development. The political-economical situation of the Eurasian Economic Union (hereinafter - EAEU) against the background of recent geopolitical changes requires special attention. Kazakhstan is one of the main participants of the Union. The current state of geopolitical changes brings new challenges and risks, requires rethinking and possibly transformation of the national foreign policy towards the EAEU and its participants. This paper is aimed at studying the potential of Kazakhstan and the political-economic aspect of Kazakhstan’s stay in the Union. Moreover, further development of the Kazakhstan in EAEU in the realities of geopolitical changes, especially against the background of anti-Russian sanctions, the conflict between Russia and Ukraine. Our findings indicate that the economic potential of Kazakhstan within Keywords: EAEU, Kazakhstan, political integration, economic integration, economic potential, trade policy.